From surveillance to action: early gains from the National Violent Death Reporting System. (14th December 2006) - Campbell, R; Weis, M A; Millet, L; Powell, V; Hull-Jilly, D; Hackman, H
Abstract : Objectives: Drawing from the experiences of individual state programs that currently participate in the National Violent Death Reporting System (NVDRS), this article reviews some of the practical benefits that may accrue from the introduction of violent death surveillance systems. Design: As a state-based surveillance system that uses multiple data sources and relies upon multiple stakeholders, the NVDRS program has fostered an array of initiatives within and among individual state programs. State-based initiatives highlighted in this article were selected on the basis of a purposive sampling strategy intended to illustrate key aspects of program development. Setting: The NVDRS state programs are in Alaska, California, Colorado, Georgia, Kentucky, Maryland, Massachusetts, New Jersey, New Mexico, North Carolina, Oklahoma, Oregon, Rhode Island, South Carolina, Utah, Virginia, and Wisconsin. Results: The NVDRS has helped to build alliances and collaborative efforts between key stakeholders, facilitated the recognition of violent death as a public health problem through outreach and media attention, acted as a catalyst for new projects, enhanced surveillance of special populations and utility for evaluation, and identified key circumstances that will target interventions in state prevention planning. Conclusions: The NVDRS has implemented data collection efforts and is beginning to produce and analyze findings. In the process of implementing the data collection system and publicizing findings, state NVDRS programs are realizing other gains that strengthen their surveillance efforts. The use of data for prevention purposes will be the ultimate indicator of program success.